Dietary Practices Among Children Aged 6-59 Months in Majengo Slum, Narok County, Kenya: A Descriptive Study - Kotonto, Asenath; Muga, Miriam; Bor, Wesley (African Journal of Nutrition and Dietetics, 2024)
Understanding the dietary practices of children aged 6-59 months is critical globally, regionally, and locally, given its profound impact on child health and development. Breastfeeding and complementary feeding are fundamental for optimal nutrition during early childhood, with persistent challenges observed, especially in urban slum settings. However, there remains a notable gap in understanding these practices within Kenya, particularly in marginalized communities such as Majengo Slum. This descriptive study aimed to examine the dietary practices among children aged 6-59 months in Majengo Slum, Narok County, Kenya, focusing on breastfeeding, complementary feeding, and meal frequency. A descriptive cross-sectional design was employed, with data collected through semi-structured questionnaires, food frequency questionnaires, 24-hour dietary recalls, and anthropometric measurements. A sample size of 341 caregiver-child pairs was determined using the Fischer formula, with systematic random sampling conducted in villages within Majengo Slums. Socio-demographic characteristics revealed a predominance of female caregivers, with a significant proportion having completed primary education and engaged in small to medium businesses. Notably, 71% of children were born at health facilities. Analysis of nutrient intake indicated disparities between observed and recommended levels, with deficiencies in energy, protein, and vitamins, and excesses in certain nutrients. Specifically, only 26% met the recommended energy intake of 1600 kcal, with 11% meeting the protein requirement of 71 g. Dietary diversity assessment revealed that 76.86% of children achieved Minimum Dietary Diversity (MDD), while only 20% regularly consumed fruits and vegetables. Minimum Meal Frequency (MMF) was influenced by caregivers' education and employment status, with children in formally employed households achieving a frequency of 40% compared to a likelihood of 50% less in households with illiterate mothers/caregivers. Targeted interventions focusing on improving dietary diversity, promoting breastfeeding and complementary feeding, and enhancing meal frequency are essential for improving child nutrition and health outcomes in marginalized communities.